Magi-1 scaffolds Na(V)1.8 and Slack K(Na) channels in dorsal root ganglion neurons regulating excitability and pain - Pryce, Kerri D. (FASEB J, 2019)
Voltage-dependent sodium (Na(V)) 1.8 channels regulate action potential generation in nociceptive neurons, identifying them as putative analgesic targets. Here, we show that Na(V)1.8 channel plasma membrane localization, retention, and stability occur through a direct interaction with the postsynaptic density-95/discs large/zonula occludens-1–and WW domain–containing scaffold protein called membrane-associated guanylate kinase with inverted orientation (Magi)-1. The neurophysiological roles of Magi-1 are largely unknown, but we found that dorsal root ganglion (DRG)–specific knockdown of Magi-1 attenuated thermal nociception and acute inflammatory pain and produced deficits in Na(V)1.8 protein expression. A competing cell-penetrating peptide mimetic derived from the Na(V)1.8 WW binding motif decreased sodium currents, reduced Na(V)1.8 protein expression, and produced hypoexcitability. Remarkably, a phosphorylated variant of the very same peptide caused an opposing increase in Na(V)1.8 surface expression and repetitive firing. Likewise, in vivo, the peptides produced diverging effects on nocifensive behavior. Additionally, we found that Magi-1 bound to sequence like a calcium-activated potassium channel sodium-activated (Slack) potassium channels, demonstrating macrocomplexing with Na(V)1.8 channels. Taken together, these findings emphasize Magi-1 as an essential scaffold for ion transport in DRG neurons and a central player in pain.—Pryce, K. D., Powell, R., Agwa, D., Evely, K. M., Sheehan, G. D., Nip, A., Tomasello, D. L., Gururaj, S., Bhattacharjee, A. Magi-1 scaffolds Na(V)1.8 and Slack K(Na) channels in dorsal root ganglion neurons regulating excitability and pain.